2020
DOI: 10.1021/acs.jpclett.0c02004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Synthesis Route on the Water Oxidation Kinetics of Hematite Photoanodes

Abstract: Operando spectroelectrochemical analysis is used to determine the water oxidation reaction kinetics for hematite photoanodes prepared using four different synthetic procedures. Whilst these photoanodes exhibit very different current / voltage performance, their underlying water oxidation kinetics are found to be almost invariant. Lower photoanode performance was found to correlate with the observation of optical signals indicative of charge accumulation in mid-gap oxygen vacancy states, indicating these states… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 42 publications
4
47
0
Order By: Relevance
“…Recently reported spectroelectrochemical measurements suggest highly similar reaction kinetics (perhaps mechanisms too) at sufficiently high bias across hematite samples which were synthesized from various routes, such as atmospheric pressure chemical vapor deposition, atomic layer deposition, and solution‐based regrowth, and treated at different temperatures ranging from 230 to 800 °C ( Figure 18a ). [ 40 ] The kinetic plots for hematite also resemble those for BiVO 4 and TiO 2 in terms of reaction order (Figure 17b). Nevertheless, these electrodes do have fundamentally distinct photoresponses.…”
Section: Performance Of Oec‐decorated Photoanodes: Dependent Factorsmentioning
confidence: 72%
See 4 more Smart Citations
“…Recently reported spectroelectrochemical measurements suggest highly similar reaction kinetics (perhaps mechanisms too) at sufficiently high bias across hematite samples which were synthesized from various routes, such as atmospheric pressure chemical vapor deposition, atomic layer deposition, and solution‐based regrowth, and treated at different temperatures ranging from 230 to 800 °C ( Figure 18a ). [ 40 ] The kinetic plots for hematite also resemble those for BiVO 4 and TiO 2 in terms of reaction order (Figure 17b). Nevertheless, these electrodes do have fundamentally distinct photoresponses.…”
Section: Performance Of Oec‐decorated Photoanodes: Dependent Factorsmentioning
confidence: 72%
“…[ 37 ] It has also been reported that stronger illumination intensities that give higher surface hole densities (above ≈1 hole nm ‐1 ) can transform the reaction mechanism from first to third order, and the third‐order reaction regime is more efficient for the OER. [ 38–40 ] Whether operating conditions have a fundamental impact on the OER mechanism at OEC‐decorated photoanodes remains an open and important question. A Marcus theory‐based theoretical microkinetic model recently proposed for the OER has opened up a new path in this direction.…”
Section: Complex Roles Of Electrocatalysts For Oer At Photoanodesmentioning
confidence: 99%
See 3 more Smart Citations